2021
DOI: 10.21203/rs.3.rs-669031/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological Effects of COVID-19 on Pregnant Women and New Mothers Living in a US Hotspot

Abstract: Background: This study investigated COVID-19 related psychological distress among expectant and new mothers, with and without infection, in metropolitan New York. It also examined the trajectories of participants' distress during pregnancy and postpartum, and the moderating effect of socioeconomic status (SES). Methods: An online survey was conducted April through June 2020 among expectant and new mothers with infants (<12 months) (N=642). Associations between infection status and psychological symptoms, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Feeling unprepared for labor and delivery was found to be associated with medical vulnerability (e.g., chronic illness or having a high-risk pregnancy), changes to prenatal care, and not having access to outdoor space (Preis et al, 2020). In a cross-sectional sample of pregnant women and new mothers, Nomura et al (2021) found that concurrent suicidal ideation and substance use was highest in women who tested positive for the virus, and that levels of distress were highest for women in the third trimester and postpartum periods. Fear of the baby contracting COVID-19, lack of social support, and higher levels of pregnancy-specific anxiety have been found to be associated with poorer overall mental health (Pope et al, 2021).…”
mentioning
confidence: 99%
“…Feeling unprepared for labor and delivery was found to be associated with medical vulnerability (e.g., chronic illness or having a high-risk pregnancy), changes to prenatal care, and not having access to outdoor space (Preis et al, 2020). In a cross-sectional sample of pregnant women and new mothers, Nomura et al (2021) found that concurrent suicidal ideation and substance use was highest in women who tested positive for the virus, and that levels of distress were highest for women in the third trimester and postpartum periods. Fear of the baby contracting COVID-19, lack of social support, and higher levels of pregnancy-specific anxiety have been found to be associated with poorer overall mental health (Pope et al, 2021).…”
mentioning
confidence: 99%
“…Postpartum women face stressful physiological and emotional changes, which have been exacerbated by the COVID-19 pandemic’s disruptive impact on access to postnatal care, isolation, and pandemic uncertainty [ 18 ]. Isolation and uncertainty during the COVID-19 pandemic yielded high rates of psychological distress in adults, including increases in panic and anxiety disorders, and increased depression symptomology [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal substance use, including both alcohol and drug use, increased in 39.2% of mothers of children ages 0–8 years-old since the onset of COVID-19 [ 23 ]. A study in New York investigated substance use for pregnant and mothers who had given birth in the prior 12 months between April and June 2020, revealing high prevalence rates of substance use for tobacco (20.7%), cannabis (15.0%), and alcohol use (38.0%) [ 18 ]. These rates are high in comparison to the prevalence rates from a study conducted in 2017 which showed lower rates for tobacco (14.7%), cannabis (7.1%), and alcohol use (11.5%) among pregnant women [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Feeling unprepared for labor and delivery was associated with medical vulnerability (e.g., chronic illness or having a high-risk pregnancy), changes to prenatal care, and not having access to outdoor space (Preis et al, 2020). In a cross-sectional sample of pregnant women and new mothers, Nomura et al (2021) found that suicidal ideation and substance use was highest in women who became infected with the virus, and that levels of distress were highest for women in the 3 rd trimester and postpartum periods. Finally, fear of the baby contracting COVID-19, lack of social support, and higher levels of pregnancy-specific anxiety have been found to be associated with poorer overall mental health (Pope et al, 2021).…”
mentioning
confidence: 99%